The First Record Of Platystele ximenae (Pleurothallidinae, Orchidaceae) For Colombia - Kolanowska, Marta (Biodiversity: Research and Conservation, 2012)
Previously known only from the type locality in Ecuador, Platystele ximenae is reported for the first time from Colombia. This species has been described and illustrated based on the material recently collected in the department of Valle del Cauca. Information about its habitat and ecology is provided.